Planting seeds of Change (New Delhi, 2017)
This book provides glimpses of an evolvin partnership between UNDP and the Government of India since the early 1950 It shows how iseeds of developmentî with collaborative projects and programmes have been nurtured by the people of India achieve transformative results and cataly growth and human development.
Keywords: International Law